What is current practice in soft tissue sarcoma grading? - Golouh, Rastko (Radiology and oncology (Ljubljana), 2001)
Purpose. Most published grading systems of soft tissue sarcomas (STS) are somewhat subjective and it seems that there is no definite consensus among experts which of them is the most effective. The aim of this study was to collect data from practicing pathologists and to get some insight in the practice of STS grading. Subjects. A questionnaire was sent to 135 pathologists chosen randomly. Results. There were 88 responders from 30 countries from 5 continents. Most responders (85%) grade STS, more frequently in Europe than in non-European countries. Three-grade system is preferred by both European and non-European pathologists, who use it in almost 77% and 67%,respectively. They apply the criteria set by FNCLCC in 37.3%, by NCI in 24%, by Broders in 12% and by Markhede in 1.4%. In Europe, FNCLCC system is the most widely used. Beside classical histological criteria, other modern methods are applied by more than one half of the responders. Immunohistochemical evaluation of proliferation markers is the method most widely used, followed by molecular markers and DNA flow cytometry. Conclusion.The results of our study indicate that most pathologists consider histologic grade of STS as a valuable, however not completely satisfactory predictor of a patients survival.
Keywords: Classification; diagnostika; histologija; Neoplasm staging; Pathology; Prognosis; Questionnaires; rak (medicina); Sarcoma; sarkom; Soft tissue neoplasms